Adiposity Indexes as Phenotype-Specific Markers of Preclinical Metabolic Alterations and Cardiovascular Risk in Polycystic Ovary Syndrome: A Cross-Sectional Study - Mario, Fernanda Missio; Graff, Scheila Karen; Spritzer, Poli Mara (Experimental and Clinical Endocrinology & Diabetes, 2017)
Polycystic ovary syndrome (PCOS) is a common condition in women of reproductive age. 2 PCOS phenotypes (classic and ovulatory) are currently recognized as the most prevalent, with important differences in terms of cardiometabolic features. We studied the performance of different adiposity indexes to predict preclinical metabolic alterations and cardiovascular risk in 234 women with PCOS (173 with classic and 61 with ovulatory PCOS) and 129 controls. Performance of waist circumference, waist-to-height ratio, conicity index, lipid accumulation product, and visceral adiposity index was assessed based on HOMA-IR ≥ 3.8 as reference standard for screening preclinical metabolic alterations and cardiovascular risk factors in each group. Lipid accumulation product had the best accuracy for classic PCOS, and visceral adiposity index had the best accuracy for ovulatory PCOS. By applying the cutoff point of lipid accumulation product<34, we identified a subgroup of patients without cardiometabolic alterations (P<0.05) in the group with classic PCOS, a population at higher risk for hypertension, dyslipidemia, and impaired glucose tolerance. In ovulatory PCOS, visceral adiposity index ≥ 1.32 was capable of detecting women with significantly higher blood pressure and less favorable glycemic and lipid variables as compared to ovulatory PCOS with lower visceral adiposity index (P<0.05). These results suggest LAP ≥ 34 as the best marker for classic PCOS, and VAI ≥ 1.32 for ovulatory PCOS women. Both indexes can be easily calculated with measures obtained in routine clinical practice and may be useful to detect cardiometabolic risk and secure early interventions.